A Study of Adsorption of Malachite Green from Aqueous Solution on Graphene Oxide/Polyvinyl Pyrrolidone/Acrylic Acid - Layth S. Jasim Al-Hayder (Journal of Global Pharma Technology, 2018)
Graphene oxide/polyvinyl pyrrolidone/acrylic acid (GO / PVP / AAc) was prepared. It is a composite hydro gel. They were synthesized by the self-assembly of polyphinylpyrolydone (PVP), acrylic acid (AAc), and Graphene oxide (GO). This composite hydro gel , GO- based , were used to remove two types of dyes , Malachite Green (MG) of its aqueous solutions. It was found that the composite hydrogel prepared have a high surface area. Various experimental variables were studied, such as, contact time (1-180 min), adsorbent surface mass (0.01-0.1 g), the initial concentration of the absorbat material (10-1000mg / L) for both two types of dyes. Also studied were the effect of each temperature, ionic strength, and pH. The experimental isotherm data were also analyzed using the linear forms of Langmuir, Freundlich, and Temkin equations, in order to determine the maximum adsorption capacity. Thermodynamic functions of Adsorption process were also studied, Gibbs free-energy (DG), Entropy (ΔS), and Enthalpy (∆H).Keywords: Adsorption, Composite, Malachite Green, Isotherms, Thermodynamic.